Controlling freeze-drying of hydrogel

JP2022171601A5Inactive Publication Date: 2025-01-30UPM KYMMENE OYJ
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2022071931
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-04-30
Filing Date
2022-04-25
Publication Date
2025-01-30
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The hydrophilic nature of nanocellulose fibrils and their tendency to aggregate during freeze-drying hinder effective drying of NFC hydrogels, leading to product damage and altered properties during long-term storage.

Method used

Adjusting the residual water content of lyophilized hydrogels by adding biomolecules such as oligosaccharides or disaccharides and controlling the freeze-drying cycle based on the glass transition temperature (Tg') to ensure successful reconstitution and maintain hydrogel properties.

Benefits of technology

Lyophilized hydrogels can be stored at room temperature for extended periods while retaining their properties and can be reconstituted to desired shapes and concentrations, suitable for cell culture applications, with reduced primary drying time and improved stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000018_0000
    Figure 00000018_0000
  • Figure 00000018_0001
    Figure 00000018_0001
  • Figure 00000018_0002
    Figure 00000018_0002
Patent Text Reader

Abstract

To provide a method for controlling freeze-drying and reconstitution of a hydrogel comprising nanoscale cellulose.SOLUTION: The present disclosure relates to a method for controlling freeze-drying of a hydrogel, where the method comprises adjusting the residual water content of the freeze-dried hydrogel. The method comprises adding a biomolecule to the hydrogel before freeze-drying the hydrogel, and / or optimizing the freeze-drying cycle, e.g., by taking into account Tg' (glass transition temperature of a maximally freeze-concentrated sample) of the mixture comprising the hydrogel and the biomolecule. The present disclosure further provides the use of a freeze-dried hydrogel composition for cell culture, a cell-culturing scaffold, and a method for manufacturing a reconstituted hydrogel.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] Field of Disclosure The present disclosure relates to a method for controlling the lyophilization of a hydrogel comprising nanoscale cellulose, the method comprising adjusting the residual moisture of the lyophilized hydrogel, and to a lyophilized hydrogel composition comprising nanoscale cellulose, at least one biomolecule selected from oligosaccharides and disaccharides, and a preferred residual moisture. The present disclosure further relates to the use of the lyophilized hydrogel composition for cell culture, a scaffold for cell culture, and a method for producing a reconstituted hydrogel.

Background Art

[0002] Background of Disclosure In recent years, cellulose-based hydrogel nanomaterials with biodegradable and biocompatible characteristics have attracted interest for different biopharmaceutical applications. Cellulose-based hydrogel nanomaterials are particularly interesting based on their intrinsic properties and similarity to physiological matrices.

[0003] In order to enable more suitable transportability of materials and improve storage characteristics at room temperature, for example, the drying of wood-based natural nanofibrillar cellulose (NFC) hydrogels has been studied.

[0004] Lyophilization, a drying method widely used to improve the storage life and handling of heat-sensitive products, is one method for preserving heat-sensitive substances. However, the hydrophilicity of the fibrils of nanocellulose and their tendency to aggregate during the drying process hinder attempts to dry NFC hydrogels. Furthermore, lyophilization can sometimes damage the product and the properties of the product can change during longer-term storage.

[0005] Despite ongoing research and development in the preservation of cellulosic hydrogel nanomaterials, there remains a need to provide improved methods for preserving hydrogels containing nanoscale cellulose. [Overview of the project]

[0006] Brief explanation of disclosure The object of this disclosure is to provide a method for controlling the lyophilization and reconstitution of a hydrogel containing nanoscale cellulose by adjusting the residual moisture content of the lyophilized hydrogel. In some embodiments of this disclosure, the method includes adding biomolecules to the hydrogel before lyophilization and / or optimizing the lyophilization cycle by considering, for example, the Tg' (glass transition temperature of the maximum freeze-concentrated sample) of the mixture containing the hydrogel and biomolecules. Typically, the hydrogel contains nanoscale cellulose, such as nanofibril cellulose, and at least one biomolecule selected from oligosaccharides or disaccharides.

[0007] This disclosure is based on the idea of ​​a desire to identify methods for controlling and maneuvering the lyophilization of hydrogels, for example, to ensure the successful reconstruction of lyophilized hydrogels and to understand molecular-level interactions with water during lyophilization.

[0008] The advantages of the method and lyophilized hydrogel composition of this disclosure are that the lyophilized hydrogel can be stored for a long period of time, exceeding one year, at room temperature (20-25°C), and can be reconstituted while maintaining the properties of the hydrogel used for lyophilization. The lyophilized hydrogel can be reconstituted to a preferred shape, concentration, and / or consistency.

[0009] A further advantage of the lyophilized hydrogel composition of this disclosure is that it can be used for cell culture and in methods for manufacturing cell culture scaffolds. Since the hydrogel concentration optimized for cell culture differs for different cells, it is advantageous that hydrogels of different concentrations can be used for lyophilization, and that the lyophilized hydrogel can be reconstituted to the original concentration or a different concentration.

[0010] A further advantage is that the method of this disclosure can significantly increase the temperature of the primary drying. This has a significant impact from a time-consuming and economic standpoint, as even a 1°C increase in the sample temperature during freeze-drying can drastically reduce the time required for primary drying.

[0011] The method disclosed herein is particularly suitable when a hydrogel containing nanoscale cellulose, such as natural nanofibril cellulose, is freeze-dried for use, for example, in cell culture. [Brief explanation of the drawing]

[0012] Brief explanation of the drawing Hereinafter, this disclosure will be described in more detail by preferred embodiments with reference to the accompanying drawings.

[0013] [Figure 1] Figure 1 shows the shear rate viscosity (mean ± SD, n=3) before lyophilization (FD) and after reconstitution of lyophilized cakes from nanofibril cellulose (NFC) hydrogel compositions containing no biomolecules (control, A), 300 mM sucrose (B), 150 mM trehalose and 333 mM glycine (C), and 300 mM trehalose (D) (mean ± SD, n=3). [Figure 2] Figure 2 shows the storage modulus (G') and loss modulus (G") before lyophilization and after reconstitution of nanofibril cellulose (NFC) compositions containing no biomolecules (control, A), 300 mM sucrose (B), and 300 mM trehalose (C) (mean ± SD, n=3). [Figure 3] Figure 3 shows the 3D viability of HepG2 cell spheroids (A) and PC3 cell spheroids (B) cultured in reconstituted lyophilized (FD) hydrogel and fresh non-lyophilized hydrogel (Cntrl); [Figure 4] Figure 4 shows the bond free energies of different monosaccharides and disaccharides studied with and without glycine molecules; [Figure 5] Figure 5 shows the penetration of water molecules into the amorphous cellulose surface of nanofibril cellulose containing 300 mM sucrose, 300 mM trehalose, and 150 mM trehalose and 333 mM glycine; and [Figure 6] Figure 6 shows SEM images of lyophilized nanofibril cellulose (NFC) formulations without excipients (NFC), containing 300 mM sucrose (NFC+SUC), containing 300 mM trehalose (NFC+TRE), and magnified images of the same compositions. [Modes for carrying out the invention]

[0014] Detailed explanation of disclosure A method for controlling the lyophilization of a hydrogel containing nanoscale cellulose is provided to enable storage at room temperature and successful reconstruction of lyophilized hydrogels, which are particularly suitable as scaffolds for cell culture.

[0015] Surprisingly, it has been found that the lyophilization and / or reconstitution of hydrogels containing nanoscale cellulose can be controlled by adjusting the residual moisture content of the lyophilized hydrogel composition. For example, it has been found that the residual moisture content of the lyophilized hydrogel composition can be adjusted and thus the reconstitution of the lyophilized hydrogel composition can be improved and controlled by using biomolecules as antifreeze or lyoprotectants when lyophilizing hydrogels containing nanoscale cellulose, such as nanofibril cellulose. Typically, the biomolecules are one or more oligosaccharides, such as trisaccharides or disaccharides, and the adjustment is made by optimizing the amount of biomolecules added to the composition.

[0016] According to some embodiments of the present disclosure, the method comprises adding biomolecules to a hydrogel containing nanoscale cellulose before freeze-drying the hydrogel. Typically, the biomolecules are selected from oligosaccharides or disaccharides, preferably disaccharides or mixtures of several disaccharides, more preferably disaccharides, most preferably lactose (4-O-β-D-galactopyranosyl-D-glucopyranose), trehalose (α-D-glucopyranosyl-α-D-glucopyranoside), or sucrose (β-D-fructofuranosyl-α-D-glucopyranoside). Trehalose and sucrose typically both have high glass transition temperatures and hydrogen bonding capabilities. Amino acids such as glycine can be added, for example, to improve the attractiveness of polysaccharides or disaccharides to cellulose. Typically, amino acids are: charged amino acids such as arginine, lysine, aspartic acid, or glutamic acid; polar amino acids such as glutamine, asparagine, serine, threonine, tyrosine, histidine, or cysteine; amphiphilic amino acids such as tryptophan, tyrosine, or methionine; or hydrophobic amino acids such as glycine, alanine, valine, isoleucine, leucine, proline, phenylalanine, or methionine, preferably one of glycine, tryptophan, leucine, and / or glutamine.

[0017] According to some embodiments of the present disclosure, the lyophilization of the hydrogel of the present disclosure can be controlled by utilizing a lyophilization cycle, by ensuring that the temperature does not exceed the glass transition temperature (Tg) of the mixture containing the hydrogel and biomolecules, taking into account the Tg' (glass transition temperature of the maximum freeze-concentrated sample).

[0018] In this specification and in the claims, the following terms have the meanings defined below.

[0019] The term nanoscale cellulose refers to nanofibril cellulose and / or nanocrystals. As used herein, the terms nanofibril cellulose, nanofibril, nanofibrilized cellulose, or NFC are understood to encompass plant-derived nanofibril structures, including fibrils and fibril bundles freed from cellulosic fibrous materials or cellulose pulp. Nanofibril structures freed from cellulosic fibrous raw materials are characterized by a high aspect ratio (length / diameter): their length may exceed 1 μm, while their diameter typically remains less than 200 nm. The smallest nanofibrils are scales of the basic fibril, with diameters typically ranging from 2 to 12 nm. The dimensions and size distribution of fibrils depend on their disintegration method and efficiency, as well as pretreatment. Typically, the median length of fibrils or fibril bundles in NFCs is less than 100 μm, e.g., in the range of 1–50 μm, and the number-average diameter of fibrils or fibril bundles is less than 200 nm, preferably in the range of 2–100 nm. Intact, unfibrillated microfibril units may be present in nanofibril cellulose, but only in negligible amounts. Nomenclature related to nanofibril cellulose is not uniform, and inconsistent terminology is used in the literature. For example, the following terms are used as synonyms for nanofibril cellulose: cellulose nanofiber, nanofibril cellulose (CNF), nanofibrillar cellulose, nanoscale fibrillated cellulose, microfibril cellulose, cellulose microfibril, microfibrillated cellulose (MFC), and fibril cellulose. As used herein, nanofibril cellulose does not imply the inclusion of non-fibril rod-shaped cellulose nanocrystals or whiskers. Nanocrystals are highly crystalline materials also known as cellulose nanocrystals (CNC), cellulose nanocrystals (NCC), or cellulose nanowhiskers (CNW).The nanocrystals are rod-shaped, hard, have a narrow size distribution, and are shorter than the nanofibrils. The nanocrystals also have a lower viscosity and yield strength and do not retain water as well as nanofibril cellulose.

[0020] The term biomolecule, also called biological molecule, is a substance produced by cells and organisms. Biomolecules have a wide range of sizes and structures, as well as various functions. The four major types of biomolecules are carbohydrates, lipids, nucleic acids, and proteins. As used herein, the particularly relevant biomolecules are carbohydrates, preferably oligosaccharides such as trisaccharides and disaccharides. Disaccharides can be reducing sugars such as lactose, maltose and cellobiose, or non-reducing disaccharides such as trehalose and sucrose, and preferably the disaccharide is a non-reducing disaccharide.

[0021] Also, amino acids can be used as biomolecules together with oligosaccharides and / or disaccharides. Amino acids can be charged amino acids such as arginine, lysine, aspartic acid, or glutamic acid; polar amino acids such as glutamine, asparagine, serine, threonine, tyrosine, histidine, or cysteine; amphiphilic amino acids such as tryptophan, tyrosine, or methionine; or hydrophobic amino acids such as glycine, alanine, valine, isoleucine, leucine, proline, phenylalanine, or methionine.

[0022] Typically, the lyophilization process is divided into three main steps: 1) freezing (solidification of the sample), 2) primary drying (sublimation of frozen water), and 3) secondary drying (removal of unfrozen water).

[0023] The term "freezing step" refers to the first step of freeze - drying, where the temperature of the composition is lowered below its freezing point to solidify the sample. The freezing of an aqueous solution or general crystallization consists of two steps: 1) nucleation, and 2) growth of the nuclei into macroscopic crystals. The driving force for nucleation is mainly determined by supercooling. When the temperature drops below the freezing point of the solution, the probability of forming thermodynamically favorable ice clusters that function as nuclei for ice crystallization increases.

[0024] The term "primary drying" refers to the main step of drying and is usually the longest stage in the freeze - drying process. During the primary drying step, the frozen solid water (ice) of the sample is sublimated under reduced pressure. The driving force for sublimation is the vapor pressure difference (temperature difference) between the frozen water and the condenser surface.

[0025] The term "secondary drying" refers to the final part of freeze - drying where any unfrozen water still present in the sample is removed. Since ice is removed during primary drying, thus minimizing the risk of melting or collapse, secondary drying can be carried out at a higher temperature. For amorphous materials in particular, the temperature increase is preferably carried out with a slow ramp (about 1 °C / min) to avoid collapse.

[0026] The dryness, i.e., the water content (or residual water content) of the freeze - dried product, is typically determined by gravimetric analysis. The amount of water is determined by subtracting the dry weight from the initial weight. Next, the water content is calculated as the amount of water divided by the dry weight or the total weight, depending on the reporting method. Another way to describe dryness is the content of dry substance (DS content), also called the dry matter content. DS is the percentage of solids in a mixture of substances, and the unit of DS content is % by weight. The higher this ratio, the drier the mixture.

[0027] The term residual water refers to water in a freeze-dried composition that is not released during secondary drying, i.e., residual water remaining in / on a freeze-dried hydrogel composition containing nanoscale cellulose such as nanofibril cellulose. The residual water content of a freeze-dried hydrogel composition containing nanoscale cellulose such as nanofibril cellulose can be measured by Karl Fischer titration. Water that is not released from the composition during primary drying but is removed during secondary drying is called bound water.

[0028] The term glass transition temperature (Tg') of a maximum freeze-concentrated sample refers to the temperature at which the composition undergoes a glass transition, i.e., the temperature at which the freeze-concentration of the solute increases the viscosity of the solution to the point where solid ice can no longer be formed.

[0029] The term "reconstitution" refers to the process of restoring a dried substance to its original state by adding a reconstitution medium, such as water and / or cell culture medium. Reconstitution can restore the substance to its original state or to a different concentration or stiffness, for example, by adding less reconstitution medium than the amount of water released.

[0030] According to embodiments of the present disclosure, nanoscale cellulose is selected from nanofibril cellulose and / or nanocrystals, preferably from natural nanofibril cellulose and / or nanocrystals, more preferably nanoscale cellulose is nanofibril cellulose, most preferably natural nanofibril cellulose. In a hydrogel containing nanofibril cellulose, the total fiber content is typically 0.5% to 5%, preferably 0.7% to 3%, more preferably 0.8% to 2.5%, most preferably about 0.8% or 2% (m / v).

[0031] Typically, in embodiments of the present disclosure, the freeze-drying method comprises a freeze step, primary drying, and secondary drying. According to some embodiments of the present disclosure, freeze-drying is After gradually lowering the temperature at 0.5 to 2°C / min, preferably about 1°C / min, a freezing process is carried out at ATM pressure for 1 to 5 hours at a temperature preferably between -40°C and -60°C. Primary drying and / or a primary drying process in which the temperature is raised to a temperature between -40°C and -50°C at a rate of 0.5 to 2°C / min, preferably about 1°C / min, the pressure is reduced to a pressure between 30 mTorr and 100 mTorr, preferably about 50 mTorr, and then the temperature is maintained for 2 to 120 hours, preferably 10 to 100 hours, more preferably 50 to 100 hours. Secondary drying involves gradually increasing the temperature from a temperature between -40°C and -50°C to room temperature (+20°C to 25°C) at a rate of 0.5 to 2°C / min, preferably about 1°C / min, and maintaining that temperature for 0.5 to 5 hours, preferably 1 to 2 hours. This includes the following. Primary drying can be determined by comparative pressure measurements using a capacitance manometer (absolute pressure, CM) and a pirani gauche (relative pressure reduction).

[0032] Typically, in embodiments of the present disclosure, hydrogel compositions are prepared by mixing biomolecules of different concentrations with water, such as ultrapure water, e.g., MQ water, which is then combined with a hydrogel containing nanoscale cellulose, such as nanofibril cellulose, up to a desired total fiber content (m / v). Alternatively, the biomolecules are added as part of a method for producing nanofibril cellulose prior to freeze-drying. Preferably, the hydrogel compositions are homogenized by conventional techniques, e.g., by mixing them using a vortex, or for higher concentration compositions using syringe techniques. The total concentration of biomolecules in the hydrogel composition is selected from an amount typically between 100 mM and 700 mM, preferably between 150 mM and 500 mM, and more preferably between 150 mM and 300 mM, of the total concentration of the mixture, and the amount is selected from a range between 100 mM, 125 mM, 150 mM, 175 mM, 200 mM, 225 mM, 250 mM, 275 mM, 300 mM, 325 mM, 350 mM, 375 mM, 400 mM, 425 mM, 450 mM, 475 mM, 500 mM, 550 mM, 600 mM, 650 mM, and 700 mM.

[0033] The method disclosed herein typically involves the following steps: a) A step of providing a hydrogel containing nanoscale cellulose; b) A step of providing at least one biomolecule selected from oligosaccharides, disaccharides, or any combination thereof; c) A step of mixing the hydrogel from step a) with the biomolecules from step b) to obtain a mixture; and d) A step of freeze-drying the mixture from step c) to obtain a freeze-dried hydrogel containing nanoscale cellulose. Includes.

[0034] The lyophilization of hydrogels is controlled by the methods of this disclosure. Lyophilized hydrogel compositions typically include hydrogels containing nanoscale cellulose and biomolecules. It has been shown that the residual water content of lyophilized hydrogel compositions can be adjusted to control the reconstitution of the lyophilized hydrogel. Without being constrained by any explanatory model, preliminary observations suggest that biomolecules penetrate nanoscale cellulose, thereby creating more space on the nanoscale cellulose by increasing the surface area on which water molecules can more readily bind and / or permeate the cellulose structure, while the addition of biomolecules to nanoscale cellulose before lyophilization results in a detachment effect in addition to binding water to themselves. The stronger the attraction of biomolecules to amorphous NFCs, the more water passes through the system.

[0035] Lyophilized hydrogel compositions are also provided, each comprising nanoscale cellulose and at least one biomolecule selected from oligosaccharides and disaccharides, and the residual moisture content of the lyophilized hydrogel composition is 0.2% (w / w) to less than 2% (w / w), preferably 0.2% to 1.9%, more preferably 0.3% to 1.6%, and most preferably 0.5% to 1.3%. Typically, in embodiments of the present disclosure, the lyophilized hydrogel composition comprises individual fibrous ribbons. Depending on the intended use, the lyophilized hydrogel composition is typically lyophilized on a support, preferably in or on a bag, bottle, column, syringe or well plate, more preferably on a glass vial, 48-well plate, 96-well plate, 384-well plate or 1536-well plate. Storage is carried out in a moisture-free, sealed package. Depending on the intended use, storing or preserving a substantially dry, lyophilized hydrogel composition powder, i.e., aerogels by the methods, processes, and products of the present disclosure, offers several advantages compared to the storage and preservation of wet hydrogels. Aerogels become hydrogels upon rehydration. In one embodiment of the present disclosure, varying amounts of lyophilized nanocellulose are present in wells. Adding the same amount of water or cell culture medium to each well provides a test panel with different cell culture concentrations.

[0036] The methods and products of this disclosure can also be used to provide lyophilized hydrogel microparticles or lyophilized hydrogel droplets that can be reconstituted into microbeads; to provide lyophilized hydrogel membranes, i.e., aerogel membranes, that can be lyophilized as sheets or in a mold and then moistened, i.e., reconstituted into hydrogel scaffolds or soft membranes; or to provide pre-filled microchips containing lyophilized hydrogels that can be moistened before use or used to form a concentration gradient to enable various cell culture conditions. One type of hydrogel scaffold of this disclosure is a rigid membrane reconstituted with a higher solids content, typically 3% to 5%, preferably 3% to 4% (m / v) of nanofibril cellulose. Hydrogel scaffolds can be stacked, for example, to constitute a co-culture system with cells on top between the scaffolds. Furthermore, lyophilized hydrogels can be mixed with powdered active pharmaceutical ingredients (APIs) using nanocellulose as a dispersant when moistened.

[0037] According to embodiments of the present disclosure, the mole fraction of residual water is 5% to 25%, preferably 6% to 20%, more preferably 9% to 15% of the lyophilized hydrogel composition; the mole fraction of biomolecules is 50% to 90%, preferably 55% to 85%, more preferably 60% to 80% of the lyophilized hydrogel composition; and / or the mole fraction of nanoscale cellulose is 3% to 40%, preferably 10% to 35%, more preferably 15% to 30% of the lyophilized hydrogel composition, wherein the nanoscale cellulose is preferably nanofibril cellulose.

[0038] Furthermore, a freeze-dried hydrogel composition that can be obtained by the method of this disclosure is provided.

[0039] Reconstitution of a lyophilized hydrogel composition involves adding a reconstitution medium to the lyophilized hydrogel composition. The reconstitution medium is typically water and / or cell medium or a mixture thereof. It may also include the addition of other substances or elements, such as cells; buffers such as phosphate-buffered saline (PBS); reinforcing agents; covering agents; activators; and / or salts such as NaCl. The volume of the reconstitution medium depends on the desired hydrogel concentration. Typically, the volume corresponds to the volume of water lost during lyophilization, but it can also be adjusted to be optimal for a particular cell type, for example.

[0040] A preferred use of the lyophilized hydrogel compositions of this disclosure is for cell culture. In embodiments of this disclosure, the cells are typically prokaryotic or eukaryotic cells, preferably differentiated or undifferentiated eukaryotic cells, more preferably totipotent, pluripotent, multipotent, oligopotent, or unipotent stem cells. The cells may be, for example, hepatocellular carcinoma cell lines (HepG2), prostate cancer cell lines (PC3), or human adipose / stromal cells (hASCs). Typically, the cells can be prokaryotic or eukaryotic cells. For example, microbial cells such as bacterial cells or yeast cells may be included. Eukaryotic cells may be plant cells or animal cells. The cells may be cultured cells. Examples of eukaryotic cells include transplantable cells such as stem cells, e.g., totipotent, pluripotent, multipotent, oligopotent, or unipotent cells. In the case of human embryonic stem cells, the cells may be derived from deposited cell lines, or from unfertilized eggs, i.e., “parthenogenetic” eggs, or from parthenogenetically activated oocytes, so as not to destroy the human embryo. The cells can be maintained and proliferated on or within a hydrogel without the use of extracellular animal or human-derived chemicals. The cells can be uniformly dispersed on or within the hydrogel. Thus, examples of cells include stem cells, undifferentiated cells, progenitor cells, and fully differentiated cells, and combinations thereof. In some examples, the cells include cell types selected from the group consisting of keratocytes, keratinocytes, fibroblasts, epithelial cells, and combinations thereof. In some examples, cells are selected from a group consisting of stem cells, progenitor cells, precursor cells, connective tissue cells, epithelial cells, muscle cells, nerve cells, endothelial cells, fibroblasts, keratinocytes, smooth muscle cells, stromal cells, mesenchymal cells, immune system cells, hematopoietic cells, dendritic cells, hair follicle cells, platelets, erythrocytes, mononuclear cells, retinal pigment cells, hepatocellular carcinoma cells, and combinations thereof.

[0041] Furthermore, a cell culture scaffold is provided, which comprises a reconfigured lyophilized hydrogel composition of the Disclosure. Typically, the cell culture scaffold further comprises water and / or cell medium or a combination thereof, optionally together with cells.

[0042] A method for producing reconstituted hydrogels, such as cell culture scaffolds, is also provided, and this method involves the following steps: a) A step of providing a lyophilized hydrogel composition; b) A step to obtain a reconstituted hydrogel by adding water, cell culture medium, or a mixture thereof to the lyophilized hydrogel composition to obtain a reconstituted hydrogel. Includes.

[0043] According to embodiments of the present disclosure, the cell culture medium may contain cells, or cells may be added later in or on the cell culture scaffold. The method may further include adding other substances or elements, such as buffers or salts, such as NaCl, to or on the scaffold, or adding the cell culture medium and / or cells on top of the scaffold. [Examples]

[0044] Examples The natural nanofibrillated cellulose (NFC) hydrogel used in the examples was supplied by UPM, Kymmene, Finland. The NFC concentration was 1.5% (m / v) (GrowDex®).

[0045] Analytical methods used in the examples Rheological measurement Viscosity, loss modulus (G”), and storage modulus (G') were measured three times on selected NFC hydrogel compositions using a HAAKE Viscotester iQ Rheometer (Thermo Scientific, Karlsruhe, Germany). The instrument included a Peltier system for temperature control, and all measurements were performed at 24°C. Data from the rheological measurements were analyzed using HAAKE RheoWin 4.0 software (Thermo Fischer Scientific). Reconstituted lyophilized NFC hydrogel compositions were allowed to stand at room temperature before measurement.

[0046] For shear viscosity measurements, a plate-on-plate configuration using parallel 35 mm diameter steel was used for all selected compositions. The shear rate was increased from 0.1 to 1000 1 / s, and results were observed at 16 time points. Vibration frequency sweep analysis was performed using a double-cap configuration with parallel 25 mm diameter steel. A constant amplitude sweep was performed before measurement to determine the linear viscoelastic region. A constant angular frequency ω=1 Hz was used at vibration stresses between 1*10⁻⁴ and 500 Pa. Based on the linear viscoelastic region, the selected vibration stress was τ=1.5 Pa for all selected NFC hydrogel compositions, and the angular frequency range was 0.6 to 125.7 rad s⁻¹. Results from modulus (moduli) were observed at 37 time points.

[0047] Freeze-drying protocol Freeze-drying was performed using a laboratory-scale freeze-dryer, Lyostar II (SP Scientific Inc., USA). Different freeze-drying cycles were used based on the Tg' temperature of the different NFC hydrogel compositions.

[0048] Evaluation of reconstitution of lyophilized hydrogels After freeze-drying, the elegance of the formed cake was evaluated, and the freeze-dried NFC hydrogel composition was reconstituted with ultrapure water to the starting volume immediately after opening the vial cap. The rate of reconstitution of the dried composition into hydrogel and the maintenance of compositional uniformity were evaluated. Bubbles formed in the reconstituted hydrogel were removed by centrifugation for 1 minute (1000 rpm).

[0049] Residual moisture The residual water content of lyophilized NFC hydrogel compositions was measured using an automated colorimetric Karl Fischer titrator (Metrohm, 899 Coulometer, Switzerland). Hydranal (Coulomat AG, Fluca) was used as the solvent for the measurement. The lyophilized NFC hydrogel composition was diluted with 1 ml of methanol, drawn into a 0.8 ml syringe, and then injected into the bath flask of the Karl Fischer titrator. The results were shown in micrograms of water, and the water content of the methanol was treated as a blank in the calculations. The mass percentage and mole fraction of residual water content in the lyophilized composition were manually calculated. All measurements were performed three times.

[0050] Scanning electron microscope (SEM) The morphology of lyophilized NFC hydrogel compositions was studied using a scanning electron microscope (SEM) Quanta FEG250 (FEI Company, USA). Sample preparation was performed manually by cutting the sample with tweezers for detection of internal structure and surface analysis. The sample was placed on double-sided carbon tape coated with silver paint. Before imaging, the sample was sputtered with platinum for 25 seconds using an Agar sputtering apparatus (Agar Scientific Ltd., UK). The homogeneity of the reconstructed lyophilized NFC hydrogel compositions was evaluated using an optical microscope (Leica microsystems, Germany).

[0051] Example 1: Evaluation of different hydrogel compositions, optimization of rheological and physicochemical properties of lyophilized hydrogels. Natural nanofibrillated cellulose (NFC) hydrogel with a fiber content of 1.5% (m / v) was provided by UPM, Kymmene, Finland (GrowDex® trademark). All chemicals used in this study, D-(+)-trehalose dihydrate, sucrose, and glycine (99%), were purchased from Sigma Aldrich, USA.

[0052] All NFC hydrogel compositions studied were prepared by mixing different concentrations of trehalose, sucrose, or combinations thereof with ultrapure water (MQ water), and then combining them with NFC hydrogels until a total fiber content of 0.8% (m / v) was achieved. The total concentrations of biomolecules in the NFC hydrogel compositions ranged from 50 mM to 1000 mM. The NFC hydrogel compositions were then homogenized by vortex mixing, and compositions of biomolecules at concentrations higher than 600 mM were mixed using a syringe technique based on the protocol from Paukkonen H. et al. ("Nanofibrillar cellulose hydrogels and reconstructed hydrogels as matrices for controlled drug release", International journal of pharmaceutics 532 (2017) 269-280). NFC hydrogels with a fiber content of 0.8% (m / v) and free of biomolecules or organic solvents were used as controls.

[0053] The physicochemical properties of NFC hydrogel compositions were evaluated by measuring osmotic pressure and pH. The osmotic pressure of the reconstituted lyophilized compositions was measured using a manual freezing point osmometer (Osmomat 3000, Gonotech). The osmometer was calibrated to 0 mOsmol / kg with ultrapure water and then to 100–850 mOsmol / kg with a calibration standard (NaCl, Gonotech). For measurement, the sample was pipetted into the measuring container (Gonotech) and then placed on the upper probe of the instrument. The pH of all reconstituted lyophilized NFC hydrogel compositions was measured using pH paper (Macherey-Nagel, Germany). Measurements were repeated after lyophilization and reconstitution.

[0054] To optimize the freeze-drying temperature, the glass transition temperature (Tg') of all NFC hydrogel compositions and controls was measured by differential scanning calorimetry (DSC) (TA Instruments). NFC hydrogel compositions were pipetted into sealed T-Zero pans (40 μl). Measurements were performed by first lowering the temperature from +40°C to -80°C, and then heating to +20°C at 10°C / min with a cell-purge gas flow (N2) of 50 ml / min. Temperature and heat flow were calibrated with indium. Three glass transition temperature measurements were performed, and the results were analyzed using TRIOS software (TA Instruments). Two NFC hydrogel compositions containing 150 mM trehalose, 333 mM glycine, and 700 mM DMSO or glycerol, with a Tg' lower than -50°C, were excluded.

[0055] Freeze-drying was performed using a laboratory-scale freeze-dryer, Lyostar II (SP Scientific Inc., USA). Two different freeze-drying cycles were used based on the Tg' temperatures of different NFC hydrogel compositions. The freezing process was carried out at -55°C / -47°C (1°C / min) for 2 hours, followed by increasing the temperature at 1°C / min to -50°C / -42°C and decreasing the pressure to 100 mTorr / 50 mTorr. Primary drying was determined by comparative pressure measurements using a capacitance manometer (absolute pressure, CM) and a pirani gauche (relative pressure reduction). Freeze-drying was then continued to secondary drying, where the temperature was gradually increased from -50°C / -47°C to +20°C at 1°C / min. The total length of the first freeze-drying cycle was 54 hours, and the second was 143 hours. Sample volume was 0.2 ml or 1.75 ml, depending on the experiment. The NFC hydrogel composition was lyophilized in 2 ml or 6 ml Schott Toplyo® injection vials (Adelphi), depending on the sample size. The vials were sealed with rubber Daikyo D Sigma lyophilization stoppers (Adelphi). After lyophilization, an All-Aluminium Crimp seal (West Pharmaceutical Services) was placed in the vial. The lyophilized samples were stored at +4°C before further experiments.

[0056] The cakes of lyophilized NFC hydrogel compositions containing 150 mM trehalose and 666 mM glycine collapsed, while those containing 750 mM–1000 mM trehalose showed shrinkage. Slight cracking of the formed cakes was observed in the lyophilized controls and lyophilized NFC hydrogel compositions containing 50 mM–250 mM sucrose or trehalose. Elegant, white solid cakes were obtained using lyophilized NFC hydrogel compositions containing 300 mM sucrose and / or trehalose, as well as those containing 150 mM trehalose and 333 mM glycine.

[0057] Lyophilized (FD) NFC hydrogel compositions were reconstituted with ultrapure water (MQ water) to a starting volume immediately after opening the vial cap. The rate of reconstitution of the FD composition into hydrogel and the maintenance of uniformity of the NFC composition were evaluated.

[0058] The reason they were excluded was that they failed to dissolve the collapsed and shrunk cakes when the original volume of ultrapure water was added. Furthermore, the freeze-dried controls formed aggregates after reconstruction, which could not be homogenized.

[0059] After reconstitution of the lyophilized NFC hydrogel composition, which had the appearance of a successful cake, the color of the cake immediately changed to transparent, and the hydrogel was formed after 2 minutes of gentle manual stirring. To remove the air bubbles formed inside the reconstituted lyophilized NFC hydrogel composition, the sample was centrifuged (1000 rpm) for 1 minute, after which they corresponded to the NFC hydrogel composition before lyophilization.

[0060] The physicochemical properties were evaluated by measuring the osmotic pressure and pH of reconstituted lyophilized NFC hydrogel compositions containing different concentrations of trehalose, sucrose, and glycine. Osmotic pressure increased with increasing biomolecular concentration, with compositions containing trehalose or sucrose between 50 mM and 300 mM having corresponding osmotic pressures between 50 mOsmol / kg and 300 mOsmol / kg. A slight decrease in osmotic pressure was observed after lyophilization and reconstitution of all NFC hydrogel compositions.

[0061] Optical microscope images showed similar homogeneity between the reconstituted lyophilized NFC composition containing biomolecules and the pre-lyophilized NFC composition containing biomolecules. However, optical microscope images after the lyophilization process showed unorganized, crystalline features, and therefore homogeneity could not be observed from the reconstituted lyophilized control.

[0062] Reconstituted lyophilized NFC hydrogel compositions containing both 300 mM trehalose and sucrose had osmotic pressures higher than the calibration range of 0–850 mOsmol / kg and were excluded from subsequent experiments. The pH of all compositions was between 6 and 7 and remained the same after lyophilization and reconstitution.

[0063] After optimizing the freeze-drying process, the retained properties of the hydrogel and reconstituted freeze-dried NFC compositions had to be ensured.

[0064] Based on the organized porous structure of the freeze-dried cakes, viscosity measurements were performed on three different reconstituted freeze-dried NFC hydrogel compositions containing 300 mM sucrose or trehalose, and one containing 150 mM trehalose and 333 mM glycine. Oscillatory frequency sweep analysis was performed on the last two compositions containing only 300 mM sucrose or trehalose, based on viscosity measurements and a more suitable Tg' temperature above -40°C.

[0065] The addition of biomolecules did not significantly affect the viscosity properties of the NFC hydrogel compositions before lyophilization, which decreased linearly with increasing shear rate. Unlike the reconfigured lyophilized control in Figure 1A, the presence of biomolecules in the reconfigured lyophilized NFC hydrogel formulations preserved shear viscosity, as observed from Figures 1B-D. The sucrose-containing composition in Figure 1A, or the glycine and trehalose combination in Figure 1B, exhibited identical viscosity properties before and after lyophilization.

[0066] The viscoelastic properties of the last two reconstituted lyophilized NFC hydrogel compositions containing 300 mM sucrose or trehalose, and those of the control, were studied. As shown in Figures 2A–C, the G' before lyophilization was equal between the NFC hydrogel compositions containing biomolecules and those without biomolecules, with their G'' being higher. As shown in Figure 2A, after lyophilization and reconstitution, the modulus of the control crossed over with each other and was significantly different from that before lyophilization. As shown in Figure 2B, the reconstituted lyophilized NFC hydrogel composition containing 300 mM sucrose had the same G' modulus as the one before lyophilization. As shown in Figure 2C, the G' of the reconstituted lyophilized NFC hydrogel composition containing 300 mM trehalose was slightly reduced compared to the same composition before the lyophilization process.

[0067] To ensure that the remaining compositions were properly freeze-dried, the mass percentage of residual water in the freeze-dried NFC hydrogel compositions was measured. With the exception of the control, all compositions contained less than 3% (w / w) residual water.

[0068] To more accurately describe the water content of the freeze-dried materials, the mole fraction of residual water was calculated. The results are shown in Table 1. Assuming the molecular weight of NFCs to be the molecular weight of glucose monomers in the calculations, the mole fraction of water was theoretically calculated to be over 99% in all NFC hydrogel compositions before freeze-drying. After freeze-drying, the mole fraction of residual water in the freeze-dried control was measured to be approximately 35%. All freeze-dried NFC hydrogel compositions showed a mole fraction of residual water of less than 30%.

[0069] [Table 1]

[0070] As the results show, the amount of biomolecules affects residual moisture and the mole fraction of residual water. Therefore, in order to obtain a reconstituteable freeze-dried hydrogel, it is possible to optimize the residual moisture by adding different biomolecules and biomolecules to the hydrogel before freeze-drying.

[0071] Based on these results, freeze-drying of hydrogels, including NFC hydrogels, was particularly successful with NFC hydrogel compositions containing 300 mM sucrose as a biomolecule. Having sucrose as the sole cryoprotective compound with NFC hydrogels offers several advantages compared to other studied biomolecules. For example, it was possible to raise the primary drying temperature from -50°C to -42°C compared to NFC hydrogel compositions containing glycine. Furthermore, the porous and organized morphology of sucrose-containing NFC hydrogel compositions, as well as their physicochemical properties such as iso-osmotic solution, pH neutral environment, and non-toxicity, are beneficial for various applications.

[0072] Example 2 Preparation of NFC composition for cell culture Lyophilized hydrogels were prepared using 300 mM sucrose and 1.5% nanofibril cellulose (NFC). Sucrose was mixed into the NFC hydrogel, and the samples were lyophilized on a low-adhesion 96-well plate (LyoStar II, SP Scientific).

[0073] Nanofibril cellulose is a natural NFC hydrogel with a fiber content of 1.5% (m / v) provided by UPM, Kymmene in Finland (GrowDex® trademark), and sucrose was purchased from Sigma Aldrich in the USA.

[0074] The freeze-drying cycle was as follows: Freezing was performed by lowering the temperature at a rate of 1°C / min until it reached -47°C. Freezing was continued at ATM for 3 hours. Primary drying was carried out at a temperature of -42°C and a pressure of 50 mTorr (6.67 Pa) for 94 hours. During secondary drying, the temperature was gradually increased by raising it from -42°C to 20°C at a rate of 1°C / min. The pressure was 50 mTorr (6.67 Pa), and secondary drying was continued for 1.5 hours. The freeze-dried hydrogel was packaged, sealed to protect it from air moisture, and stored at room temperature for several months.

[0075] Example 3 Culture of 3D cell spheroids in lyophilized and reconstituted NFC hydrogel The suitability of the lyophilized and reconstituted NFC hydrogels from Example 2 for 3D cell culture was studied. The cells studied were hepatocellular carcinoma cell lines (HepG2), prostate cancer cell lines (PC3), and human adipose-derived / stromal cells (hASCs).

[0076] Lyophilized 1.5% NFC hydrogel samples were directly reconstituted at different NFC concentrations. Samples were reconstituted with MQ water, NaCl, cell medium, and / or cell mixtures. pH was controlled to be within the physiological range. The cell medium was a nutrient mixture buffered with bicarbonate containing fetal bovine serum. For reconstituted lyophilized hydrogels with MQ water alone, the volume used was the volume of water lost during lyophilization. For mixtures of MQ water and cell medium, the amount of MQ water was the volume of water lost during lyophilization, and in the case of cell medium, it was the amount required for dilution.

[0077] The NFC hydrogel concentration of the reconstituted hydrogel containing MQ water, cell medium, and cells was adjusted to the optimal hydrogel stiffness for the selected cell type. The concentrations used were 0.8%, 1.0%, and 0.125% for HepG2, PC3, and hASC cells, respectively. The storage modulus (G') and loss modulus (G") of the reconstituted composition were measured using Viscotester (Thermo Scientific) and compared to those of the raw hydrogel. The molar osmotic concentration was measured using Osmomat 3000 (Gonotec) and optimized for cell culture (280–320 mOsmol / kg) by changing the composition of the reconstituted medium. It was concluded that the molar osmotic concentration, pH, storage modulus, and loss modulus of the reconstituted NFC hydrogel composition remained unchanged after lyophilization and reconstitution. Reconstitution of natural NFC to different natural NFC concentrations after lyophilization was possible regardless of the initial concentration of natural NFC.

[0078] The reconstituted NFC hydrogel, culture medium, and cells were mixed by pipetting, and reservoir medium was added to the top of the hydrogel-cell-suspension. 3D cell spheroids were cultured in CO2 at 37°C using a previously established protocol (as described in Bhattacharya et al., “Nanofibrillar cellulose hydrogel promotes three-dimensional liver cell culture”, Journal of controlled release: official journal of the Controlled Release Society. 164 (2012) 291-8), and the same protocol was used for both the reconstituted hydrogel and the non-freeze-dried hydrogel used as a control. Cell spheroid viability was examined over 7 days, i.e., on days 1, 3, 5, and 7, using the alamarBlue cell viability assay. Cell spheroid size was assessed microscopically over the 7-day study period. The results of the viability tests are shown in Figure 3A for HepG2 cell spheroids and in Figure 3B for PC3 cell spheroids. The left column shows the results of freeze-dried NFC, and the right column shows the control.

[0079] The tests demonstrated that lyophilized hydrogels can be reconstituted at different concentrations, and that the reconstituted lyophilized hydrogels are suitable for cell culture, just like the raw, non-lyophilized hydrogels. Both HepG2 and PC3 cells were successfully cultured for 7 days on lyophilized and reconstituted natural NFC hydrogels.

[0080] Example 4: Molecular Dynamics Simulation The interactions between water, excipients, and NFCs were studied using molecular dynamics (MD) simulations. MD simulations were performed to study the dynamic behavior of the system and gain insights into specific mechanisms.

[0081] Three plane-like simulation systems were developed: one with a hydrophobic surface and another with a hydrophilic surface, for crystalline cellulose to determine the bond free energy, and for amorphous cellulose to determine the effect of biomolecules on water permeation.

[0082] Excipients were added to the equilibrated water system at random positions in the aqueous phase, with concentrations based on the number of water molecules. Three new systems were then generated from each system containing the following concentrations of biomolecules: 300 mM trehalose, 150 mM trehalose with 333 mM glycine, and 300 mM sucrose. Additional simulation systems were generated for different monosaccharides and disaccharides with the following concentrations of biomolecules: 300 mM fructose, glucose, lactose, sucrose, trehalose, and xylitol, 225 mM of each sugar combined with 75 mM glycine, and 200 mM of each sugar combined with 100 mM glycine.

[0083] Three properties were particularly interesting: the difference in free energy between the excipient and the cellulose layer, the penetration of water into the amorphous system, and the sugar chain detachment effect in the crystalline system, which was observed during visualization. The difference in free energy was determined by generating the potential of the average force from the partial density of the excipient via the GMX density. The difference in free energy was quantified using the more stable side of the cellulose surface. Water penetration was calculated using GMX Select, representing the average number of water molecules within 1 nm of the planes along the x and y axes formed by the center of mass of the cellulose. The average number of glucose molecules in the same region was determined in the same way, except that it was divided by 6 using carbon molecules. Finally, GMX RMS was used for eight chains on the top and bottom surfaces of both crystalline cellulose layers to determine the RMSD of those individual chains, which gave a metric regarding chain detachment as a function of time.

[0084] The results of excipient binding to the NFC surface were consistent across different cellulose planes. Additional simulations with different monosaccharides and disaccharides showed that all sugar molecules preferred to concentrate at the NFC-water interface. However, binding strengths differed between systems. As seen in Figure 4, the highest binding free energies were recorded for sucrose and lactose. For fructose, glucose, and xylitol, low surface interactions were observed. The left column for all sugars shows the results for 300 mM sugars, the middle column shows the results for each sugar at 225 mM combined with 75 mM glycine, and the right column shows the results for each sugar at 200 mM combined with 100 mM glycine.

[0085] Glycine was shown to have no attractive force to the NFC surface. In a 300 mM concentration system, sucrose demonstrated a higher attractive force to the cellulose surface than trehalose. On the hydrophobic cellulose surface, the difference in free energy was 0.54 kJ / mol. Similarly, in systems containing half the concentration of trehalose and 333 mM glycine, the attractive force of trehalose increased slightly but significantly, with a difference in free energy of 0.56 kJ / mol. The differences with hydrophilic surfaces were 0.38 kJ / mol and 0.20 kJ / mol, respectively. Additional tests comparing 300 mM sucrose and 200 nM sucrose together with 100 mM glycine, leucine, tryptophan, or glutamine showed that amino acids generally improve the attractive force of sucrose to cellulose. Both tryptophan and glutamine penetrated the cellulose surface, but glutamine did not show any attractive force. Tryptophan showed significantly higher attractive force than sucrose. Furthermore, the hydrogen bonding between sugar and cellulose appears to increase with the addition of amino acids (excluding glycine).

[0086] Biomolecules had different effects on residual moisture. As shown in Figure 5, water molecules, unlike sugars, easily penetrated the amorphous cellulose surface despite their attractive forces. In the absence of excipients, an average of 263 (±13SD) water molecules were present in a 2nm slice of amorphous cellulose. With added sucrose, water penetration increased to 274 (±15SD). However, added trehalose had no effect (262±16SD). A reduced amount of trehalose with glycine slightly increased water penetration to 267 (±12SD). By determining the average number of glucose molecules in the same region, the following water:glucose ratios were obtained: 1.385 with pure water, 1.424 with 300mM sucrose, 1.378 with 300mM trehalose, and 1.400 with 150mM trehalose with 333mM glycine. This can be explained by the different attractive forces of biomolecules to the nanocellulose system; the stronger the attractive force of biomolecules to amorphous NFCs, the more water passes through the system. The reason for this is likely that stronger attractive forces provide more space for water molecules to access the interior of amorphous NFCs. For example, the ability of water containing sucrose to penetrate more into amorphous NFCs than trehalose may be advantageous in the reconstruction of freeze-dried NFC hydrogel compositions.

[0087] During visualization, a chain exfoliation effect was discovered in the crystalline system. Because cellulose chains are not connected between periodic images, the ends of the chains at the junctions can move freely in water. This effect was not significant in the pure water system. However, added sugars, particularly trehalose, were able to further exfoliate these chain ends into the aqueous phase. Furthermore, after detaching the chains from the crystalline structure, the sugars could move into the formed cracks, preventing the chains from returning. To quantify this effect, the root mean square deviation (RMSD) of the surface chains was determined as a function of time. The RMSD increased as the chain ends were pulled from the structured crystalline structure into the disordered aqueous phase. In the hydrophobic system, the cutoff for chains detached from the crystalline structure was ~0.15 nm, while in the hydrophilic system it was ~0.35 nm. Surface chains on hydrophilic surfaces are more mobile due to their hydrophilicity. The results indicate that trehalose and sucrose molecules can promote chain exfoliation on NFC surfaces compared to systems without excipients.

[0088] At higher magnification, fibrous structures approximately 15 nm wide were prominent in the SEM images of the freeze-dried control. Individual fibrous ribbons could also be observed in freeze-dried compositions containing sucrose or trehalose. Figure 6 shows SEM images of freeze-dried NFC compositions containing 300 mM sucrose and 300 mM trehalose, without excipients, as well as magnified images of the same compositions. Arrows indicate examples of individual fibrous ribbons observed in the compositions. This may be due to the chain-stripping ability of these biomolecules, as demonstrated in simulations of crystalline NFCs.

[0089] In light of these simulation results, it is clear that trehalose and sucrose molecules can interact with the NFC surface and alter the NFC structure by promoting surface chain exfoliation, which partially explains the experimentally recorded differences in the morphology of NFCs after freeze-drying. Although glycine does not have an attractive force to the NFC surface, the simulation highlighted the effect of glycine on bound trehalose on the NFC surface. Specifically, in the glycine-trehalose hybrid system, the binding of trehalose to the NFC surface was slightly stronger, reaching the same binding free energy value as sucrose without glycine. Furthermore, the simulation results suggest that no NFC chain exfoliation occurred on crystalline and hydrophobic NFC surfaces containing glycine, which may result in more retained stability and structure of the NFC matrix in aqueous environments before and after freeze-drying.

Claims

1. 13. A method for controlling the freeze-drying of a hydrogel comprising nanoscale cellulose, the method comprising adjusting the residual moisture of the freeze-dried hydrogel.

2. 2. The method of claim 1, characterized in that the freeze-drying comprises a freezing step, primary drying and secondary drying, and the residual moisture is water remaining in the freeze-dried hydrogel that is not released during secondary drying.

3. 2. The method according to claim 1, characterized in that the nanoscale cellulose is selected from nanofibril cellulose and / or nanocrystals, preferably from natural nanofibril cellulose and / or nanocrystals, more preferably the nanoscale cellulose is nanofibril cellulose, most preferably natural nanofibril cellulose.

4. The method comprises the steps of: a) providing a hydrogel comprising nanoscale cellulose; b) providing at least one biomolecule selected from an oligosaccharide or a disaccharide; c) mixing the hydrogel of step a) with the biomolecule of step b) to obtain a mixture; and d) freeze-drying the mixture of step c) to obtain a freeze-dried hydrogel comprising nanoscale cellulose. The method of claim 1 , comprising:

5. 5. The method according to claim 4, characterized in that the biomolecule is a disaccharide, more preferably a non-reducing disaccharide or lactose, most preferably lactose, trehalose or sucrose.

6. The method according to claim 4, characterized in that the amount of biomolecule is between 100 mM and 700 mM, preferably between 150 mM and 500 mM, more preferably between 150 mM and 300 mM of the total concentration of the mixture.

7. 2. The method according to claim 1, characterized in that the residual moisture of the lyophilized hydrogel composition is between 0.2% (w / w) and less than 2% (w / w), preferably between 0.2% and 1.9%, more preferably between 0.3% and 1.6%, most preferably between 0.5% and 1.3%.

8. A freeze-dried hydrogel composition, characterized in that the freeze-dried hydrogel composition comprises nanoscale cellulose and a biomolecule selected from oligosaccharides and disaccharides, and the residual moisture of the freeze-dried hydrogel composition is between 0.2% (w / w) and less than 2% (w / w), preferably between 0.2% and 1.9%, more preferably between 0.3% and 1.6%, and most preferably between 0.5% and 1.3%.

9. 9. The freeze-dried hydrogel composition of claim 8, wherein the freeze-dried hydrogel composition comprises individual fiber ribbons.

10. 9. The freeze-dried hydrogel composition according to claim 8, characterized in that the composition is freeze-dried on a support, preferably a bag, a bottle, a column, a syringe or a well plate, more preferably on a glass vial, a 48-well plate, a 96-well plate, a 384-well plate or a 1536-well plate.

11. 9. The freeze-dried hydrogel composition according to claim 8, characterized in that the molar fraction of residual water is between 5% and 25%, preferably between 6% and 20%, more preferably between 9% and 15% of the freeze-dried hydrogel composition.

12. 9. The lyophilized hydrogel composition according to claim 8, characterized in that the molar fraction of biomolecules is between 50% and 90%, preferably between 55% and 85%, more preferably between 60% and 80% of the lyophilized hydrogel composition.

13. 9. The freeze-dried hydrogel composition according to claim 8, characterized in that the molar fraction of nanoscale cellulose is between 3 and 40%, preferably between 10 and 35%, more preferably between 15 and 30% of the freeze-dried hydrogel composition, preferably the nanoscale cellulose is nanofibrillar cellulose.

14. A freeze-dried hydrogel composition obtainable by the process of any of claims 1 to 7.

15. Use of the freeze-dried hydrogel composition according to any of claims 8 to 13 for cell culture; for producing hydrogel microbeads; for producing hydrated sheets or membranes; for producing pre-loaded microchips; or as a dispersing agent in a mixture with active pharmaceutical ingredients.

16. 16. The use according to claim 15, characterized in that the lyophilized hydrogel is reconstituted with water; water and cell culture medium; cell culture medium; cell culture medium and cells; or water, cell culture medium and cells.

17. 16. Use according to claim 15, characterised in that the cell is a prokaryotic or eukaryotic cell, preferably a differentiated or undifferentiated eukaryotic cell, more preferably a totipotent, pluripotent, multipotent, oligopotent or unipotent stem cell.

18. A cell culture scaffold comprising a reconstituted lyophilized hydrogel composition according to any one of claims 8 to 13.

19. 1. A method of producing a reconstituted hydrogel, the method comprising the steps of: a) providing a lyophilized hydrogel composition according to any one of claims 8 to 13; b) obtaining a reconstituted hydrogel by adding a reconstitution medium comprising water, cell culture medium or a mixture thereof to the lyophilized hydrogel composition to obtain a reconstituted hydrogel. A method comprising:

20. 20. The method of claim 19, wherein the reconstituted hydrogel is used for cell culture.

21. 20. The method of claim 19, wherein the cell culture medium comprises cells.